Forest Hill Paper Company - Albright, Thomas L., 1955- (London : Institute of Management Accountants, 2008)
The Forest Hill Paper Company case is based on the author's experience with cost system design at various paper manufacturing plants. The case provides a background discussion of the industry, competitive environment, and manufacturing process. Thus, students have a realistic context in which to study the principles of activity-based costing. The case requires students to develop product cost calculations using the company's traditional system. Next, students design a simple two-stage allocation system having three cost pools. The case asks students to compare the activity-based cost calculations with the cost calculations from the traditional system. Finally, students make recommendations to management based on their knowledge obtained from the improved cost system.
Originally published in Albright, T. L. (2008). Forest Hill Paper Company. IMA Education Case Journal, 1(2), Article 4.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Forest Hill Paper Company -- Case studies; Paper industry -- Finance -- Case studies